2022
DOI: 10.1038/s41467-022-32442-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into inhibitory mechanism of human excitatory amino acid transporter EAAT2

Abstract: Glutamate is a pivotal excitatory neurotransmitter in mammalian brains, but excessive glutamate causes numerous neural disorders. Almost all extracellular glutamate is retrieved by the glial transporter, Excitatory Amino Acid Transporter 2 (EAAT2), belonging to the SLC1A family. However, in some cancers, EAAT2 expression is enhanced and causes resistance to therapies by metabolic disturbance. Despite its crucial roles, the detailed structural information about EAAT2 has not been available. Here, we report cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 75 publications
2
23
0
Order By: Relevance
“…Kato et al using point mutations showed that these residues forming the cavities are closely related to the sensitivities of the EAAT subtypes to inhibitors. 51 Indeed, the addition of an aromatic group (red in Figure 5 ) via amide bond ( 19 , IC 50 = 59 nM) increased the activity by ∼100-fold vs EAAT2. 19 was slightly more selective to EAAT2 than EAAT1(∼2-fold) and EAAT3 (and 40-fold).…”
Section: Eaat2 Inhibitorsmentioning
confidence: 98%
See 4 more Smart Citations
“…Kato et al using point mutations showed that these residues forming the cavities are closely related to the sensitivities of the EAAT subtypes to inhibitors. 51 Indeed, the addition of an aromatic group (red in Figure 5 ) via amide bond ( 19 , IC 50 = 59 nM) increased the activity by ∼100-fold vs EAAT2. 19 was slightly more selective to EAAT2 than EAAT1(∼2-fold) and EAAT3 (and 40-fold).…”
Section: Eaat2 Inhibitorsmentioning
confidence: 98%
“…Noteworthy, 26 , which is commercially available as WAY213613, remains the most selective and potent EAAT2 inhibitor to date. , Cryo-EM analysis has recently shown that WAY213613 inhibits glutamate uptake via EAAT2 by either interaction at the glutamate-binding site and sterically preventing HP2 loop movement (Figure ). The l -asparagine (Figure , blue and black squares) and 4-(2-bromo-4,5-difluorophenoxy) phenyl (Figure , green and red squares) moieties of 26 played distinct roles in the EAAT2 inhibition, by competing with the glutamate binding and sterically preventing the HP2 loop gating suspending the transport cycle of glutamate, respectively.…”
Section: Eaat2 Inhibitorsmentioning
confidence: 99%
See 3 more Smart Citations